EFFECT OF DIODE LASER ON PERIODONTITIS TREATMENT WITH ONE-VISIT ULTRAZONIC SUBGINGIVAL DEBRIDEMENT - Pongpairote, Natnicha; Srisuwantha, Rungtiwa; Laosrisin, Narongsak (Srinakharinwirot University Journal of Sciences and Technology, 2021)
This study aimed to evaluate the clinical outcome of one-visit periodontal treatment using ultrasonic piezoelectric device in combination with diode laser. Thirty patients were randomized into two groups. In both groups, sub-gingival full mouth SRP in a single visit was performed using piezoelectric ultrasonic device. In test group, after sub-gingival debridement, a 970 nm diode laser was applied to all periodontal pockets of ≥5 mm. The clinical parameters were evaluated at 1,3 and 6 months after treatment. At 6 months, each clinical parameter was significantly improved compared to baseline, better results were in favor of the test group. At 3 and 6 months, statistical significant difference between control and test group were found in bleeding on probing (BOP) at site with ≥5 mm. pocket depth and pocket reduction (p<0.05). Nevertheless, the significant difference in clinical attachment gain at site with ≥ 7 mm. pocket depth was only found after 6 months (p<0.05). The use of diode laser following subgingival SRP could shallow periodontal pocket depth and improved clinical attachment level, especially at site with ≥ 7 mm. depth of periodontal pockets